Diversity, Distribution, and Ecology of Fungi in the Seasonal Snow of Antarctica - Graciéle C.A. de Menezes; Soraya S. Amorim; Vívian N. Gonçalves; Valéria M. Godinho; Jefferson C. Simões; Carlos A. Rosa; Luiz H. Rosa (Microorganisms, 2019)
We characterized the fungal community found in the winter seasonal snow of the Antarctic Peninsula. From the samples of snow, 234 fungal isolates were obtained and could be assigned to 51 taxa of 26 genera. Eleven yeast species displayed the highest densities; among them, Phenoliferia glacialis showed a broad distribution and was detected at all sites that were sampled. Fungi known to be opportunistic in humans were subjected to antifungal minimal inhibition concentration. Debaryomyces hansenii, Rhodotorula mucilaginosa, Penicillium chrysogenum, Penicillium sp. 3, and Penicillium sp. 4 displayed resistance against the antifungals benomyl and fluconazole. Among them, R. mucilaginosa isolates were able to grow at 37 °C. Our results show that the winter seasonal snow of the Antarctic Peninsula contains a diverse fungal community dominated by cosmopolitan ubiquitous fungal species previously found in tropical, temperate, and polar ecosystems. The high densities of these cosmopolitan fungi suggest that they could be present in the air that arrives at the Antarctic Peninsula by air masses from outside Antarctica. Additionally, we detected environmental fungal isolates that were resistant to agricultural and clinical antifungals and able to grow at 37 °C. Further studies will be needed to characterize the virulence potential of these fungi in humans and animals.